The Degree of Application the Knowledge Management Strategies among the Principals of the Basic Governmental Schools at the Directorate of Education for Al- Zarqa Region the First - Shnaywer, Ammar Mahmoud; Al-momani, Yasar Ali (Journal of Educational and Psychological Sciences, 2020)
The study aimed to identify the degree of Application the Knowledge Management Strategies among the Principals at the basic governmental schools in the directorate of Education in the first Zarqa Region in Jordan, from the point of view of the male and female school teachers. The study community included all the teachers of these schools with the total number of (2915) for the academic year (2018-2019). The study sample was selected with a random stratified method. the researcher relied on a questionnaire to achieve and collected data, The results of the study has shown that the degree of application of the knowledge management strategies was moderate at these schools, and the study showed that there were statistically significant differences according to the variable of the sex variable and these differences did not appear with the variables of qualification variable. the researcher recommended to provide the requirements of application the of knowledge management strategies and to pay attention to the infrastructure and technology for schools to provide the knowledge to be able to practice the administrative skills.
Keywords: Basic schools; Knowledge management strategies; The first Zarqa Region